Comparative SILAC proteomic analysis of Trypanosoma brucei bloodstream and procyclic lifecycle stages. - Michael D Urbaniak; M Lucia S Guther; Michael A J Ferguson (PLoS ONE, 2012)
The protozoan parasite Trypanosoma brucei has a complex digenetic lifecycle between a mammalian host and an insect vector, and adaption of its proteome between lifecycle stages is essential to its survival and virulence. We have optimized a procedure for growing Trypanosoma brucei procyclic form cells in conditions suitable for stable isotope labeling by amino acids in culture (SILAC) and report a comparative proteomic analysis of cultured procyclic form and bloodstream form T. brucei cells. In total we were able to identify 3959 proteins and quantify SILAC ratios for 3553 proteins with a false discovery rate of 0.01. A large number of proteins (10.6%) are differentially regulated by more the 5-fold between lifecycle stages, including those involved in the parasite surface coat, and in mitochondrial and glycosomal energy metabolism. Our proteomic data is broadly in agreement with transcriptomic studies, but with significantly larger fold changes observed at the protein level than at the mRNA level.